In Vitro Antioxidant Activity Dpph Assay of Protein Hydrolysate Mackerel (Scomber Scombrus) Viscera - Windra Hutama Putra; Sri Subekti; Muhammad Amin (Grouper, 2024)
Based on exports data mackerel (Scomber sombrus) in 2023 approximately 2,702 tons, while by-products had produced around 60%. This creates serious problems with its disposal. Fish by-products can be processed into value-added products, one of which is fish protein hydrolysates. The purpose of the study was to determine the molecular weight of the SDS-PAGE (Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis) method and the antioxidant activity DPPH assay (2,2-diphenyl-1-picrylhydrazil) hydrolysate of mackerel viscera protein. The results showed a molecular weight in the range of 12 – 16 kDa. Antioxidant activity was shown by an inhibition percentage value of  50.117 ± 0.4793 % with an antioxidant capacity of 0.9141 ± 0.0606 mmol TE/g of Trolox equivalent samples. Based on antioxidant activity, mackerel viscera protein hydrolysate has the potential to be a natural source of antioxidants.